Girls in war, women in peace : reintegration and (in)justice in post-war Mozambique - Bunker, Lillian K (Department of Political Studies, 2015)
This study explores the longitudinal reintegration of girls involved in the post-independence war in Mozambique using in-depth qualitative research based on semi-structured interviews, and a wide range of documents. Piecing together the narratives of over 70 informants, the dissertation chronicles the way in which the war and the post-conflict environment, and to a lesser extent, the historical cultural milieu, have contributed to these women’s current realities.